Bài 15: Tìm x: c) 5(x+5)-3(x-2)=5²+18 d) 4(x+2)=3(x+1)+17 g) 3x-1=23.4 h) 4* = 64

Bài 15: Tìm x:

c) 5(x+5)-3(x-2)=5²+18 d) 4(x+2)=3(x+1)+17

g) 3x-1=23.4

h) 4* = 64

a) 198 -3(2x+4)= 120

b)2(x+7)-6=13

e) 5(x+16)=52.4

f) 22 (6x-32)-3=33

2 bình luận về “Bài 15: Tìm x: c) 5(x+5)-3(x-2)=5²+18 d) 4(x+2)=3(x+1)+17 g) 3x-1=23.4 h) 4* = 64</”

  1. Lời giải và giải thích chi tiết:
     c,5(x+5)-3(x-2) =5^2+18   d,4(x+2)=3(x+1)+17
    =>5x+25 -3x-6=25+18       =>4x+8=3x+3+17
    =>5x+(25+6)-3x=43           =>4x+8=3x+20
    =>5x + 31-3x=43                =>4x+8-8=3x+20-8
    =>(5x-3x)+31=43               =>4x=3x+12
    =>2x+31=43                       =>4x-3x=3x+12-3x
    =>2x=43-31                        =>x=12
    =>2x=12
    =>x=12:2
    =>x=6
    g,3x-1=23.4     h,4*=64        a,198-3(2x+4)=120      b,2(x+7)-6=13
    =>3x-1=92      =>4*=4^3   =>3(2x+4)=198-120    =>2x+14-6=13
    =>3x=92+1     =>x=3          =>3(2x+4)=78             =>2x+8=13
    =>3x=93                              =>2x+4=78:3               =>2x=13-8
    =>x=93:3                              =>2x+4=26                  =>2x=5
    =>x=31                                =>2x=26-4                  =>x=5:2
                                                 =>2x=22                     =>x=2,5
                                                 =>x=22:2
                                                =>x=11
    e,5(x+16)=52.2        f,22(6x-32)-3=33
    =>5(x+16)=104      =>132x-704-3=33
    =>5x+80=104         =>132x-704=33+3
    =>5x=104-80         =>132x-704 =36
    =>5x=24                =>132x=36+704
    =>x=24:5              =>132x=740
    =>x=4,8                =>x=740:132
                                  =>x=5.606….

    Trả lời
  2. $\text{c) 5(x + 5) – 3(x – 2) = 5² + 18}$
    $\text{⇔ 5x + 25 – 3x + 6 = 25 + 18}$
    $\text{⇔ 2x + 6 = 18}$
    $\text{⇔ 2x = 12}$
    $\text{⇔ x = 6}$
    $\text{Vậy: x = 6}$
    $\text{d) 4(x + 2) = 3(x + 1) + 17}$
    $\text{⇔ 4x + 8 = 3x + 3 + 17}$
    $\text{⇔ 4x + 8 = 3x + 20}$
    $\text{⇔ x = 12}$
    $\text{Vậy: x = 12}$
    $\text{g) 3x – 1= 23 . 4 }$
    $\text{⇔ 3x – 1 = 92}$
    $\text{⇔ 3x = 93}$
    $\text{⇔ x = 31}$
    $\text{Vậy: x = 31}$
    $\text{h) $4^x$ = 64}$
    $\text{⇔ $4^x$ = 4³}$
    $\text{⇔ x = 3}$
    $\text{Vậy: x = 3}$
    $\text{a) 198 – 3(2x + 4) = 120 }$
    $\text{⇔ 198 – 6x – 12 = 120}$
    $\text{⇔ 186 – 6x = 120}$
    $\text{⇔ 6x = 66}$
    $\text{⇔ x = 11}$
    $\text{Vậy: x = 11}$
    $\text{b)2(x + 7) – 6 = 13 }$
    $\text{⇔ 2x + 14 – 6 = 13}$
    $\text{⇔ 2x + 8 = 13}$
    $\text{⇔ 2x = 5}$
    $\text{⇔ x = 2,5}$
    $\text{Vậy: x = 2,5}$
    $\text{e) 5(x + 16) = 52 . 4 }$
    $\text{⇔ 5x + 80 = 208}$
    $\text{⇔ 5x = 128}$
    $\text{⇔ x = 25,6}$
    $\text{Vậy: x = 25,6}$
    $\text{f) 22(6x – 32) – 3 = 33 }$
    $\text{⇔ 22(6x – 32) = 36}$
    $\text{⇔ 6x – 32 = $\dfrac{18}{11}$}$
    $\text{⇔ 6x = $\dfrac{370}{11}$}$
    $\text{⇔ x = $\dfrac{185}{33}$}$
    $\text{Vậy: x = $\dfrac{185}{33}$}$

    Trả lời

Viết một bình luận

Câu hỏi mới